2006
DOI: 10.1002/j.2161-0045.2006.tb00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Career Counseling on French Adults: An Experimental Study

Abstract: This research project is focused on theoretical and empirical works analyzing the effects of career counseling. This experimental and longitudinal study has been carried out in France; it compares a sample of individuals having undertaken competence assessment with a control group and deals with self-esteem, self-analysis, self-concept, and the participants' situations. The results correspond to the authors' main hypotheses: The effect size calculated for all the variables (+0.62) is similar to the one observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
21
0
2
Order By: Relevance
“…for career decidedness, .18 for both career planning and vocational identity, and .39 for career exploration. With French clients, Bernaud, Gaudron, and Lemoine (2006) found the overall effect size decreased from .62 at post-test to .44 at the 6-month follow-up. Verbruggen and Sels (2008) found at the 6-month follow-up to career counseling in Belgium that scores on selfawareness and career self-directedness remained consistent with post-counseling scores but career adaptability decreased.…”
Section: Measuring Intervention Outcomementioning
confidence: 87%
“…for career decidedness, .18 for both career planning and vocational identity, and .39 for career exploration. With French clients, Bernaud, Gaudron, and Lemoine (2006) found the overall effect size decreased from .62 at post-test to .44 at the 6-month follow-up. Verbruggen and Sels (2008) found at the 6-month follow-up to career counseling in Belgium that scores on selfawareness and career self-directedness remained consistent with post-counseling scores but career adaptability decreased.…”
Section: Measuring Intervention Outcomementioning
confidence: 87%
“…Despite variations in geographic location and industry, the studies included in this synthesis all reported that protégé and mentor experiences positively influence job satisfaction (Bernaud et al, 2006;Collins, 1994 15 ; Seibert, 1999;Pan, Sun, & Chow, 2011;Gong, Chen, & Yang, 2014). For example, based on the written responses from individuals in the technical training, administration, trade, and communication industries in France, Bernaud et al (2006) found that for individuals who received career guidance, fulfillment at work seemed to be the most 15 Professionals who had been both a protégé and a mentor had the highest level of career satisfaction, followed by those who had been a protégé but not a mentor, those who had not been a protégé but had been a mentor, and those who had been neither a protégé nor a mentor.…”
Section: Subjective Measuresmentioning
confidence: 99%
“…In addition, the relevance and applicability of these studies is also tenuous as only a handful of studies focus on the student population, and of those only a few focus specifically on STEM (2004;Fouad, 1995;Kerr & Robinson Kurpius;Stoeger et al, 2013). Based upon the available evidence, however, career counseling and employment services do seem to be effective in increasing subjective outcomes such as career initiative, career self-efficacy, and career satisfaction (Bernaud et al, 2006;Brennan, 2009;Chang & Feng, 2014;Collins, 1994;Fouad, 1995;Gong et al, 2014;Kerr & Robinson Kurpius, 2004;Pan et al, 20011;Perdix et al, 2013;Siebert, 1999;Stoeger et al, 2013;Wu et al, 2013). However, the results of studies evaluating the impact of career counseling and employment services on increasing objective outcomes such as earnings, career advancement, or employment are mixed (Chang & Feng, 2014;Collins, 1994;Dar & Tzannatos, 1999;Dorsett, 2006;Gong et al, 2014;Reenen, 2004;Rodriguez-Planas, 2007;Watts, 2009).…”
Section: Limitations and Implicationsmentioning
confidence: 99%
“…The effects of the “Competencies Elicitation Career Counseling” were largely investigated in studies using applied research methodology. They reveal positive results in terms of self‐concept development, building an occupational project, and developing the ability to shape one's own career (Ferrieux, 1995; Bernaud, Gaudron, & Lemoine, 2006; Vonthron & Lagabrielle, 2003; Saint‐Jean, Mias, & Bataille, 2003).…”
Section: Counseling Psychology: Instituting a Theoretical Fieldmentioning
confidence: 99%